Multiple routes of drug administration and HIV risk among injecting drug users. - Vorobjov, Sigrid; Uusküla, Anneli; Des Jarlais, Don C; Abel-Ollo, Katri; Talu, Ave; Rüütel, Kristi (Journal of substance abuse treatment, 2012)
This study assesses relationships between drug administration routes and HIV serostatus, drug use, and sexual behaviors among current injecting drug users (IDUs) in Tallinn, Estonia. We recruited 350 IDUs for a cross-sectional risk behavior survey. Adjusted odds ratios (AORs) were calculated to explore injection risk behavior, sexual behavior, and HIV serostatus associated with multiple route use. Focus groups explored reasons why injectors might use non-injecting routes of administration. Those reporting multiple drug administration routes were less likely to be HIV seropositive (AOR = 0.49, 95% confidence interval [CI] = 0.25-0.97) and had almost twice the odds of having more than one sexual partner (AOR = 1.90, 95% CI = 1.01-3.60) and of reporting having sexually transmitted diseases (AOR = 2.38, 95% CI = 1.02-5.59). IDUs who engage in noninjecting drug use may be reducing their risk of acquiring HIV though sharing injection equipment, but if infected may be a critical group for sexual transmission of HIV to people who do not inject drugs.
Keywords: Adult; Confidence Intervals; Drug Overdose; Estonia; Female; Focus Groups; HIV Infections; HIV Seropositivity; Humans; Male; Risk; Risk Factors; Sexually Transmitted Diseases; Smoking; Socioeconomic Factors; Substance Abuse, Intravenous; Unsafe Sex